A STUDY OF THE NUCLEOLAR MATERIAL IN SCIARA COPROPHILA - Gabrusewycz-Garcia, Natalia (The Rockefeller University Press, 1966)

(untitled)
In the polytene chromosomes of Sciara coprophila, in addition to a nucleolus, large numbers of nucleolarlike structures or micronucleoli are formed. A detailed mapping localized the nucleolar organizer at one end of the X chromosome and revealed that approximately 18% of the bands of each chromosome are potentially capable of producing micronucleoli. Most of these sites are in regions known from a previous study to show asynchronous DNA replication: DNA puffs and certain heterochromatic regions. Micronucleoli are rarely found in association with bulbs. The RNA metabolism of the polytene chromosomes during late fourth instar was studied using radioautographic techniques. Isolated glands were incubated in tritiated uridine for 10 to 30 min, and radioautographs were made of squash preparations. Despite the wide range of variation found among different larval cultures, the following pattern was observed. Just prior to and at the beginning of DNA puff formation, a period of intense extrachromosomal nucleolar and micronucleolar RNA synthesis occurs. After maximal development of the DNA puffs, the synthesis of extrachromosomal RNA is at a low point, while incorporation into bulbs and DNA puffs remains high. With the onset of the prepupal stage, all nuclear RNA synthesis ceases.